Effects of ultrasonic waves on enhancement of relative volatilities in methanol-water mixtures - Ripin, Adnan; Abdul Mudalip, Siti Kholijah; Mohd. Yunus, Rosli (Penerbit UTM Press, 2008)
The application of ultrasonic wave in various fields including separation process has increased predominantly. This paper reports the practicability of using ultrasonic wave to enhance separation of binary mixtures by distillation. The binary mixture utilized was methanol-water. The effect of different ultrasonic intensity at 50, 100, 200 and 250 W/A.cm2 with frequency of 40 kHz to vapor-liquid equilibrium (VLE) of methanol-water was investigated to obtain the most suitable operating intensity. Experimental studies were also carried out to investigate the frequency effect (25 and 68 kHz) to VLE data. It was found that the use of ultrasonic wave enhanced the separation process by increasing the relative volatility of components. The highest average relative volatility of methanol-water at 29.413 was obtained from experimental study using intensity 200 W/A.cm2 and frequency of 25 kHz. The changes in relative volatility and VLE were caused by cavitational activities and vacuum effect that occur during transmission of ultrasonic wave in liquid medium. The results from this study proved the practical feasibility of using ultrasonic wave to enhance separation of binary mixtures in distillation column.